2017
DOI: 10.1111/obr.12631
|View full text |Cite
|
Sign up to set email alerts
|

The role of glucagon in weight loss‐mediated metabolic improvement: a systematic review and meta‐analysis

Abstract: Aims This meta-analysis aimed to investigate the role of glucagon suppression in regulating glucose homeostasis following diet or bariatric surgery. Methods A comprehensive search of intervention and observational studies was conducted in Medline, Scopus, Web of Science, PubMed and Embase. Random effects model meta-analysis was performed. Primary outcomes were (i) body weight change, (ii) fasting glucagon, (iii) fasting glucose and (iv) fasting insulin concentrations. Results Twenty articles reporting data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
(380 reference statements)
2
4
1
Order By: Relevance
“…Additionally, the FMO3 is suppressed by insulin, and also increased by glucagon37 which is secreted from pancreatic α-cells to promote the elevation of blood glucose 39. Both the suppression of glucagon and insulin resistance are in parallel with weight loss and act together to improve the glucose homeostasis following a weight-loss diet intervention 40. These previous studies support our observation that the association of TMAO with insulin sensitivity might be partially affected by adiposity.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the FMO3 is suppressed by insulin, and also increased by glucagon37 which is secreted from pancreatic α-cells to promote the elevation of blood glucose 39. Both the suppression of glucagon and insulin resistance are in parallel with weight loss and act together to improve the glucose homeostasis following a weight-loss diet intervention 40. These previous studies support our observation that the association of TMAO with insulin sensitivity might be partially affected by adiposity.…”
Section: Discussionsupporting
confidence: 87%
“…Kramer et al hypothesized that cross‐reactivity of the glucagon assays with other PGDPs, especially oxyntomodulin, may have contributed to the difference in results 18 . In the current study, we used a state‐of‐the‐art, novel, well‐validated glucagon assay that did not cross‐react with oxyntomodulin, and showed a non‐differential decrease in glucagon concentrations during the MMTT after weight loss in both the placebo and actively treated groups, which is consistent with a previous weight‐loss trial 19 and a recent meta‐analysis showing a decrease in fasting glucagon after weight loss 20 . We also showed that MPGF is regulated in a manner similar to glucagon in humans.…”
Section: Discussionsupporting
confidence: 84%
“…Our study highlights that the changes in glucagon and MPGF may predominately occur through weight loss. Weight loss has pleiotropic effects and may alter alpha cell secretory products via improvements in insulin sensitivity and reduction in insulin concentration 19,20 or additional hormones. Decrease in glucagon concentration has also been suggested to be a defence mechanism to increase hunger during energy restriction 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fasting plasma glucagon decreases in obese subjects after weight loss. Both bariatric surgery and dietary intervention result in comparable reduction in fasting plasma glucagon level [91].…”
Section: Excessive Glucagon Secretion Is Present In Subjects With Impmentioning
confidence: 97%